The context dependence of beneficiary feedback effects on benefactors in plant facilitation. Issue 2 (2nd July 2014) - Schöb, Christian; Callaway, Ragan M.; Anthelme, Fabien; Brooker, Rob W.; Cavieres, Lohengrin A.; Kikvidze, Zaal; Lortie, Christopher J.; Michalet, Richard; Pugnaire, Francisco I.; Xiao, Sa; Cranston, Brittany H.; García, Mary‐Carolina; et al.
Summary Facilitative effects of some species on others are a major driver of biodiversity. These positive effects of a benefactor on its beneficiary can result in negative feedback effects of the beneficiary on the benefactor and reduced fitness of the benefactor. However, in contrast to the wealth of studies on facilitative effects in different environments, we know little about whether the feedback effects show predictable patterns of context dependence. We reanalyzed a global data set on alpine cushion plants, previously used to assess their positive effects on biodiversity and the nature of the beneficiary feedback effects, to specifically assess the context dependence of how small‐ and large‐scale drivers alter the feedback effects of cushion‐associated (beneficiary) species on their cushion benefactors using structural equation modelling. The effect of beneficiaries on cushions became negative when beneficiary diversity increased and facilitation was more intense. Local‐scale biotic and climatic conditions mediated these community‐scale processes, having indirect effects on the feedback effect. High‐productivity sites demonstrated weaker negative feedback effects of beneficiaries on the benefactor. Our results indicate a limited impact of the beneficiary feedback effects on benefactor cushions, but strong context dependence. This context dependence may help to explain the ecological and evolutionary persistence of this widespread facilitative system.